Transformation of Religious Moderation and Islamic Law: Reflections on Siri' Na Pesse Culture in Bugis Community - Fikri; Rahmawati; Aris; Hannani (Al-Ulum, 2023)
This study discusses the transformation of religious moderation and Islamic law: a reflection of siri’ na pesse culture in Bugis community. The research methodology is qualitative, descriptive analytical, normative theological approach, normative juridical and formal, socio-anthropological, data analysis with religious moderation, al-urf and maqasid al-syariah theory in Islamic law. The research results show that siri’ na pesse is constructed with various pappaseng which function as advice and benchmarks in Bugis community to strengthen solidarity, unity, create harmony, order, peace and peace in community life. Religious moderation and Islamic law are one unit to maintain human harmony, foster love through siri’ na pesse as an inner bond, thoughts, and foster hearts to forgive each other, be full of understanding, eliminate hatred, violence, radicalism, extremism, and terrorism in good human relations.